Modelling the volcanic ash plume from Eyjafjallajökull eruption (May 2010) over Europe: evaluation of the benefit of source term improvements and of the assimilation of aerosol measurements - Plu, Matthieu; Bigeard, Guillaume; Sič, Bojan; Emili, Emanuele; Bugliaro, Luca; Amraoui, Laaziz; Guth, Jonathan; Josse, Beatrice; Mona, Lucia; Piontek, Dennis (2021)
Numerical dispersion models are used operationally worldwide to mitigate the effect of volcanic ash on aviation. In order to improve the representation of the horizontal dispersion of ash plumes and of the 3D concentration of ash, a study was conducted using the MOCAGE model during the EUNADICS-AV project. Source term modelling and assimilation of different data were investigated. A sensitivity study to source term formulation showed that a resolved source term, using the FPLUME plume-rise model in MOCAGE, instead of a parameterised source term, induces a more realistic representation of the horizontal dispersion of the ash plume. The FPLUME simulation provides more concentrated and focused ash concentrations in the horizontal and the vertical dimensions than the other source term. The assimilation of MODIS Aerosol Optical Depth has an impact on the horizontal dispersion the plume, but this effect is rather low and local, compared to source term improvement. More promising results are obtained with the continuous assimilation of ground-based lidar profiles, which improves the vertical distribution of ash and helps to reach realistic values of ash concentrations. The improvement can remain several hours after and several hundred kilometers away downstream to the assimilated profiles.